Hubungan Penggunaan Gadget Dan Tingkat Stress Dengan Kualitas Tidur Pada Remaja - Salwa Destya Susiana; Solehudin Solehudin; Syarifah Syarifah (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Teenagers today often experience sleep disturbances, this happens because teenagers prefer to be in front of screens such as gadgets, televisions and computers. In a day, teenagers use gadgets for 5-7 hours, so it takes around 60 minutes longer to fall asleep. Apart from using gadgets, another factor that can affect sleep quality is stress. The aim of the study was to determine the relationship between gadget use and stress levels with sleep quality in adolescents at Puspita Medika Tapos Health Vocational School, Depok. Method: This research uses an analytical design with a cross sectional approach. The sampling technique used was a total sampling of 99 students. Results: based on statistical logistic regression tests on 99 respondents, a significant value of p = 0.045 was obtained, namely <0.05 for the gadget use variable and p = 0.001, namely <0.05 for stress levels. Conclusion: there is a relationship between gadget use and stress levels with sleep quality in teenagers at Puspita Medika Vocational School.